The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1680/jbibn.15.00012
|View full text |Cite
|
Sign up to set email alerts
|

Complex poly(lactic acid)-based biomaterial for urinary catheters: II. Biocompatibility

Abstract: The present paper is focused on the surface and bulk characterization of poly(lactic acid) (PLA)-based composites that contain hydrolyzed collagen as a biological polymer, silver nanoparticles and vitamin E and epoxidized soybean oil as a plasticizer. The bionanocomposites were obtained by melt processing and evaluated for structural and surface characteristics, biocompatibility, functional properties such as antimicrobial and antioxidant activity and hydrolytic degradation behavior. It has been established th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…60 The average surface composition of two samples given in Table 6 is close to the experimental one. 60 determined from DSC and differential thermal analysis (DTA) curves ( Figure 9 and Table 7).…”
Section: Morphologysupporting
confidence: 70%
See 1 more Smart Citation
“…60 The average surface composition of two samples given in Table 6 is close to the experimental one. 60 determined from DSC and differential thermal analysis (DTA) curves ( Figure 9 and Table 7).…”
Section: Morphologysupporting
confidence: 70%
“…The multifunctionality and biocompatibility characteristics are evidenced by the results given in the second part of this research work. 60 Your contribution will be forwarded to the author(s) for a reply and, if considered appropriate by the editorin-chief, will be published as a discussion in a future issue of the journal.…”
Section: Resultsmentioning
confidence: 99%
“…[ 83 ] have shown that cell (fibroblast) spreading appeared to be dependent on the polar surface free energy. Cell spreading is low when the SFE’s polar part of the material is lower than 5 mN/m, and marked spreading occurs when is higher than 15 mN/m [ 43 ]. Based on the values of the SFE polar part determined for the PLA/R composites, it can be assumed that the sample incorporating all the components (PLA/PEG/0.5R) will give better spreading and division of the fibroblasts because their takes an intermediary value.…”
Section: Resultsmentioning
confidence: 99%
“…For more details on the method see references [ 38 , 39 ]. To determine the surface free energy (SFE) components, the CA at equilibrium between the film surface and three pure liquids (in addition to water, methylene iodide, and formamide were used, as-purchased at maximum obtainable purity) were measured by fitting the drop profile using the Young-Laplace equation [ 40 , 41 , 42 , 43 ]. The acid/base (LW/AB) approach of van Oss and Good, see Equation (4) [ 44 , 45 ], was used to calculate the total SFE and its components, namely the dispersive component, also named the Lifshitz–van der Waals interaction, ( ) and polar Lewis acid-base interactions ( ), respectively, see Equation (5).…”
Section: Methodsmentioning
confidence: 99%
“…For more details on the method, see references [81,82]. To obtain the components of the surface free energy (SFE) and the total SFE of the polymer films, the CA at equilibrium between the film surface and three pure liquid, twice-distilled water, formamide and methylene iodide (as purchased at maximum obtainable purity), was measured by fitting the drop profile using the Young-Laplace equation [82,83,84,85]. The total and the components of SFE were calculated by using the Lifshitz-van der Waals acid/base approach of van Oss and Good [86], which divides the total SFE into dispersive Lifshitz-van der Waals interactions (γsvLW) and polar Lewis acid-base interactions (γsvAB) (Equation (8)).…”
Section: Methodsmentioning
confidence: 99%